Enhancing Anterior Esthetics with Alveolar Ridge Preservation And Guided Implant Placement – A Case Report - Rana, A; Pradhan, S; Gorkhali, RS; Koirala, PK; Bartaula, B (Journal of Nepalese Prosthodontic Society, 2024)
Alveolar ridge preservation procedures are utilized to prevent loss of tissue volume in an extraction site following tooth removal. Guided implant placement utilizes surgical templates to ensure the precise positioning of implants, leading to optimal alignment and integration with the surrounding bone. This case report aims to demonstrate the effectiveness of combining alveolar ridge preservation with guided implant placement for enhancing outcomes in the anterior maxillary region following tooth extraction in a 25-year-old patient with satisfactory results.